Strategi Komunikasi Dinas Pariwisata Kota Palembang Dalam Membangun Kampung Kreatif - Umi Chalzhum Caniago; Achmad Syarifudin; Muhammad Randicha Hamandiac (CV. ITTC INDONESIA, 2023)
A communication strategy is needed to produce a communication process that can be understood by the recipient of the information in achieving goals. Therefore, the organization/or company must develop an appropriate communication strategy so that the message conveyed to the target object can be understood well. The research was conducted to analyze the performance of the Tourism Department in implementing the strategy of the Creative Village, especially in the communication aspect, because there are still many villages that do not participate in Creative Village activities, this is due to the lack of understanding of the village community about what, the purpose, why and the elements of the Creative Village itself. Therefore, the researcher wrote the thesis entitled